المسؤلية التقصيرية في مهنة الطب العلاجي - Asmuni Muhammad Thahir (Millah: Journal of Religious Studies, 2004)
As a comprehensive religion, Islam draws up the general teaching and rule relating with healthy. This teaching or rule becomes mujtahid’s reference in maintaining the doctor's medical responsibility toward their patient. In this article, the author explains that according to ulama', the responsibility is placed  on the doctor because of  his carelessness in performing his profession. Whereas other opinion states that the responsibility is caused by the existence o f  contract between medical patient and hospital. In relation with operation, the author also  explains that according to fuqaha’, the doctor can be free of  any responsibilities if  he fulfills two requirements both, that the operation was carried out by professional doctor and didn't overstep the normal bounds like cutting something not to do.